Legal, Regulatory and Governance Issues in Islamic Finance - Wilson, Rodney (Edinburgh guides to Islamic finance., 2012)
From Iran, where all banking is Shari'ah compliant, to Malaysia and the gulf, where Islamic financial institutions compete with conventional banks, Rodney Wilson examines how Islamic financial institutions are licensed and governed by common and civil law. Covering Islamic banks, takaful operators, fund management and Shari'ah compliant securities, it examines how their assets and liabilities differ from their conventional counterparts and what the implications are for risk management.